PdAgCuMt alloy and three-dimensional nano material prepared based on alloy
Through the series of processing technology of PdAgCuMt alloy, nanocrystalline three-dimensional nanomaterials were prepared, which solved the problem that traditional alloyed materials could not meet the high performance requirements, and achieved the preparation of nanomaterials with high strength, high hardness, high corrosion resistance and precision resistance characteristics.
Patent Information
- Application Number
- CN202510622087.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-08-29
AI Technical Summary
The existing technology has failed to effectively prepare metal-based nanostructured materials, and cannot meet the comprehensive performance requirements of high-function chips, loading aerospace and nuclear energy engineering. Traditional alloyed materials cannot meet the new service environment.
Three-dimensional nanomaterials with nanocrystalline structures are prepared by vacuum induction smelting, directional solidification, hot forging and cold forging, solid solution treatment and alloy aging treatment, including nano-crystalline nanomaterials, including nano-blocks, nanorods, nano-wire wires or nanoribbons.
The preparation of nanomaterials with high strength, high hardness, high elasticity and high corrosion resistance is achieved, which reduces manufacturing costs and does not require special amorphous equipment, and the process is simplified and easy to perform.
Smart Images

Figure CN120555859A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of metal-based three-dimensional nanomaterials, and in particular relates to a PdAgCuMt alloy and a three-dimensional nanomaterial prepared based on the alloy. Background Art
[0002] The research on nanotechnology and nanomaterials began in the early 1990s. After more than 20 years of global technological breakthroughs, nanotechnology and nanomaterials have made great progress, such as: (1) the chip lithography process has been improved from the original 180 nanometers to 3 nanometers; (2) the human blood vessel scavenger (nanorobot) has been successfully developed; (3) targeted drugs for treating tumors (0-dimensional nanocore-shell materials) have been successfully developed; (4) carbon nanotubes (one-dimensional) and multilayer graphene (two-dimensional) have been mass-produced; (5) various two-dimensional inorganic non-metallic structural layers such as optical films, super-hard films, and protective films have been developed. In 1994, Professor Lu Ke of the Institute of Metal Research, Chinese Academy of Sciences, first proposed the theory of "preparing bulk metal nanomaterials by crystallization of amorphous materials" in [Material.Sci.Eng.Reports]. However, so far, there has been no report on the engineering application of this technology. In addition, the methods commonly used in scientific papers, such as "preparing nanomaterials by equal-diameter bending extrusion", "preparing nanomaterials by ultrafine powder pressing and molding" and "preparing nanomaterials by 3D printing technology", have failed to provide effective analytical data and pictures and have not been recognized by the academic community. Therefore, metal-based nanostructured materials in the true sense have not yet been launched on the market.
[0003] When metal materials possess nanostructured characteristics, the relative density of their alloys and the density of grain boundaries within their microstructures increase simultaneously, while internal structural defects in the metal are significantly reduced. As a result, metal nanomaterials can exhibit extremely high mechanical properties, corrosion resistance, and stable conductivity. The development of high-performance chips, aerospace, and nuclear engineering technologies has placed higher technical demands on the comprehensive performance of metal materials. Traditional alloying materials are no longer able to meet the requirements of these new service environments, making the development of new metal nanostructured materials imperative. Summary of the Invention
[0004] Purpose of the invention: The present invention provides a PdAgCuMt alloy and a novel three-dimensional nanomaterial based on the alloy, wherein the alloy can obtain a nanocrystalline structure after a series of processing techniques.
[0005] Technical solution: The PdAgCuMt alloy of the present invention comprises the following elements by mass fraction: Pd 38-42wt%, Ag 26-30wt%, Cu 28-32wt%, Mt 1-2wt% and inevitable impurities; wherein the Mt is a combination of any two of the three elements In, Zn and Al.
[0006] The alloy composition ratio of the present invention is: 38-42wt% Pd, 26-30wt% Ag, 28-32wt% Cu, and 1-2wt% Mt (In+Zn or In+Al or Zn+Al). This alloy composition can form an infinite solid solution structure under certain thermodynamic conditions, ensuring that the alloy material can obtain nanocrystals after a series of processing steps. Specifically, based on the PdAgCu alloy, adding a small amount of the metal element In can improve the alloy's wettability and reduce its resistivity; adding a small amount of the metal element Zn can improve the alloy's fluidity and reduce its resistivity; adding a small amount of the metal element Al can improve the alloy's corrosion resistance and reduce the alloy's quenching temperature. The combined addition of any two trace elements can enhance the alloy's mechanical properties and improve its processing performance.
[0007] Furthermore, the PdAgCuMt alloy of the present invention can be prepared into a rod blank by the following steps: alloying elements are proportioned and placed in a vacuum induction melting furnace, isothermally refined at 1300-1350°C for 15-20 minutes, and then directionally solidified to obtain a rod blank.
[0008] Furthermore, the PdAgCuMt alloy of the present invention can be prepared into a cylindrical billet by the following steps: the alloying elements are proportioned and placed in a vacuum induction melting furnace, isothermally refined at 1300-1350°C for 15-20 minutes, and then cast into a round billet of the desired size.
[0009] The present invention is based on a three-dimensional nanomaterial prepared from the above-mentioned PdAgCuMt alloy. The three-dimensional nanomaterial is a block with nanocrystals and is prepared by the following steps: a round cast billet is subjected to hot forging, solid solution treatment, cold forging deformation treatment and alloy aging treatment to obtain a nanocrystal block; wherein the deformation amount of the cold forging deformation is 10-15%.
[0010] The present invention is based on a three-dimensional nanomaterial prepared from the above-mentioned PdAgCuMt alloy. The three-dimensional nanomaterial is a rod with nanocrystals and is prepared by the following steps: a round cast billet is subjected to hot rolling, solid solution treatment, cold drawing deformation treatment and alloy aging treatment to obtain the nanocrystalline rod; wherein the deformation amount of the cold drawing deformation treatment is 20-40%.
[0011] The present invention is based on a three-dimensional nanomaterial prepared from the aforementioned PdAgCuMt alloy. This three-dimensional nanomaterial is a nanocrystal-containing filamentary alloy material, produced by the following steps: a rod blank is subjected to a solution treatment, a cold drawing deformation treatment, and an alloy aging treatment to produce a nanocrystalline rod. Preferably, the solution treatment temperature decreases from 930°C to 870°C, and the cold drawing deformation is 30-50%.
[0012] The present invention is based on a three-dimensional nanomaterial prepared from the aforementioned PdAgCuMt alloy. The three-dimensional nanomaterial is a nanocrystal-containing strip material produced by the following steps: hot rolling a round ingot, solution treatment, cold rolling deformation, and alloy aging treatment to produce a nanocrystal rod. Preferably, the solution treatment temperature decreases from 930°C to 870°C, and the cold rolling deformation is 40-60%.
[0013] Beneficial effects: Compared with the existing technology, the significant advantages of the present invention are: the PdAgCuMt alloy component can form an infinite solid solution structure under certain thermodynamic conditions, and then only conventional vacuum melting furnaces, air forging hammers, two-roll rolling mills, drawing machines, wire drawing machines and ordinary heat treatment furnaces can be used to complete the preparation of PdAgCuMt metal nanomaterials, including nano blocks, nano rods, nano wires or nano strips, and the PdAgCuMt metal nanomaterials have high strength, high hardness, high elasticity, high corrosion resistance and precise resistance characteristics. The preparation process is simplified and easy, and no special equipment for manufacturing amorphous materials is required, thereby reducing the manufacturing cost of nanomaterials. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a transmission electron microscope morphology of the PdAgCuMt alloy nano-bulk material prepared in the present invention;
[0015] Figure 2 This is a transmission electron microscope morphology image of the PdAgCuMt alloy nanorods prepared in the present invention;
[0016] Figure 3 This is a transmission electron microscope morphology of the PdAgCuMt alloy nanowire prepared in the present invention;
[0017] Figure 4 This is a transmission electron microscope morphology image of the PdAgCuMt alloy nanobelt prepared in the present invention. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0019] The PdAgCuMt alloy of the present invention comprises the following elements by mass fraction: 38-42 wt% Pd, 26-30 wt% Ag, 28-32 wt% Cu, 1-2 wt% Mt, and unavoidable impurities; wherein Mt is any combination of In, Zn, and Al (the ratio can be 1:1), such as In+Zn, In+Al, or Zn+Al.
[0020] Based on the PdAgCuMt alloy, a rod billet of Φ3-8 mm or a round billet of Φ30-50 mm can be prepared.
[0021] When preparing a Φ3-8mm rod blank, it can be made through the following steps:
[0022] (1) The alloying elements are mixed in proportion and placed in a vacuum induction melting furnace for isothermal refining for 15-20 minutes at a vacuum degree of 20-50 Pa and a temperature of 1300-1350°C;
[0023] (2) A Φ3-8 mm rod blank is produced by directional solidification molding using a dummy rod at a drawing speed of 0.1-5 mm / min and a cooling water temperature of 20-30°C.
[0024] When preparing a Φ30-50mm round casting, it can be made by the following steps: the alloy elements are mixed in proportion and placed in a vacuum induction melting furnace, and after isothermal refining for 15-20 minutes under vacuum degree 20-50Pa and temperature 1300-1350℃, it is directly cast into a Φ30-50mm cylindrical billet.
[0025] In order to further verify that the PdAgCuMt alloy of the present invention can be prepared into a three-dimensional nanomaterial with nanocrystals, the following examples are tested and demonstrated based on the three-dimensional nanomaterial.
[0026] Example 1 PdAgCuMt (In+Zn) alloy bulk nanomaterial
[0027] The preparation method of the PdAgCuMt alloy bulk nanomaterial prepared in this embodiment includes the following steps:
[0028] (1) Alloy ingredients: Pd 39% (390g), Ag 28% (280g), Cu 31% (310g), InZn 2% (20g), totaling 1000g; wherein, in InZn, In accounts for 50% and Zn accounts for 50%.
[0029] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1320℃ and refine for 15min. When the vacuum in the furnace reaches 50Pa, turn off the vacuum pump, fill the furnace with high-purity argon gas, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0030] (3) Ingot casting: The furnace body is repeatedly tilted at an angle of 30 degrees for 5-7 times (mechanical stirring), and then the molten metal is poured into a water-cooled metal mold at a rate of 40g / s to produce a Φ40×80mm ingot; wherein the mold cooling water temperature is 25℃;
[0031] (4) Alloy forging: The Φ40×80 mm ingot was heated to 920°C in a box-type resistance furnace for 30 min, and then quickly forged into a 50×50×40 mm square billet.
[0032] (5) Alloy solution treatment: Place the hot forged billet into a box-type heat treatment furnace, heat to 890-920℃ and keep warm for 30min, then take it out of the furnace and quickly water quench;
[0033] (6) Alloy cold deformation: The solutionized block is placed under the forging hammer and beaten with a size of 50 × 50 mm, and then refined to the required block size of 56 × 56 × 32 mm;
[0034] (7) Alloy aging treatment: Place the cold-deformed block material in a box-type heat treatment furnace, heat it to 315°C and keep it warm for 40 minutes to obtain a block material with nanocrystals.
[0035] Example 1-1: PdAgCuMt (In+Al) alloy bulk nanomaterial
[0036] The PdAgCuMt alloy bulk nanomaterial is also prepared by vacuum casting, hot and cold forging and other processes, including the following steps:
[0037] (1) Alloy ingredients: Pd 39% (390g), Ag 28% (280g), Cu 31% (310g), InAl 2% (20g), totaling 1000g; wherein, in InAl, In accounts for 50% and Al accounts for 50%.
[0038] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1320℃ and refine for 15min. When the vacuum in the furnace reaches 50Pa, turn off the vacuum pump, fill the furnace with high-purity argon gas, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0039] (3) Ingot casting: The furnace body is repeatedly tilted at an angle of 30 degrees for 5-7 times (mechanical stirring), and then the molten metal is poured into a water-cooled metal mold at a rate of 40g / s to produce a Φ40×80mm ingot; wherein the mold cooling water temperature is 25℃;
[0040] (4) Alloy forging: The Φ40×80 mm ingot was heated to 920°C in a box-type resistance furnace for 30 min, and then quickly forged into a 50×50×40 mm square billet.
[0041] (5) Alloy solution treatment: Place the hot forged billet into a box-type heat treatment furnace, heat to 890-920℃ and keep warm for 30min, then take it out of the furnace and quickly water quench;
[0042] (6) Alloy cold deformation: The solutionized block is placed under the forging hammer and beaten with a size of 50 × 50 mm, and then refined to the required block size of 56 × 56 × 32 mm;
[0043] (7) Alloy aging treatment: Place the cold-deformed block material in a box-type heat treatment furnace, heat it to 315°C and keep it warm for 40 minutes to obtain a block material with nanocrystals.
[0044] Example 1-2: PdAgCuMt (Zn+Al) alloy bulk nanomaterial
[0045] The PdAgCuMt alloy bulk nanomaterial is also prepared by vacuum casting, hot and cold forging and other processes, including the following steps:
[0046] (1) Alloy ingredients: Pd 39% (390g), Ag 28% (280g), Cu 31% (310g), ZnAl 2% (20g), totaling 1000g; wherein, in ZnAl, Zn accounts for 50% and Al accounts for 50%.
[0047] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1320℃ and refine for 15min. When the vacuum in the furnace reaches 50Pa, turn off the vacuum pump, fill the furnace with high-purity argon gas, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0048] (3) Ingot casting: The furnace body is repeatedly tilted at an angle of 30 degrees for 5-7 times (mechanical stirring), and then the molten metal is poured into a water-cooled metal mold at a rate of 40g / s to produce a Φ40×80mm ingot; wherein the mold cooling water temperature is 25℃;
[0049] (4) Alloy forging: Heat the Φ40×80 mm ingot to 920°C in a box-type resistance furnace for 30 min, take it out and quickly forge it into a 50×50×40 mm square billet;
[0050] (5) Alloy solution treatment: Place the hot forged billet into a box-type heat treatment furnace, heat to 890-920℃ and keep warm for 30min, then take it out of the furnace and quickly water quench;
[0051] (6) Alloy cold deformation: The solutionized block is placed under the forging hammer and beaten with a size of 50 × 50 mm, and then refined to the required block size of 56 × 56 × 32 mm;
[0052] (7) Alloy aging treatment: Place the cold-deformed block material in a box-type heat treatment furnace, heat it to 315°C and keep it warm for 40 minutes to obtain a block material with nanocrystals.
[0053] The PdAgCuMt alloy nano-bulk materials prepared in Example 1, Example 1-1 and Example 1-2 were subjected to composition testing. The results obtained are shown in Table 1 below. The test results of their properties are shown in Table 2 below.
[0054] Table 1 PdAgCuMt alloy component content (wt%)
[0055]
[0056] Table 2 PdAgCuMt alloy bulk material properties (≮)
[0057]
[0058] At the same time, the block materials prepared by Examples 1, 1-2 and 1-3 of the present invention were subjected to corrosion tests. Compared with stainless steel or other corrosion-resistant alloys, they are more difficult to corrode during metallographic tests, and their structure can only be displayed after 10 minutes of etching under the conditions of 80% concentrated sulfuric acid + 10% concentrated nitric acid + 10% hydrofluoric acid, indicating that they have high corrosion resistance.
[0059] Example 2 PdAgCuMt (In+Zn) alloy nanorods
[0060] In Example 2, the process of preparing a nanocrystalline rod by vacuum casting, hot rolling, drawing, etc. includes the following steps:
[0061] (1) Alloy ingredients: Pd 40% (600g), Ag 27% (405g), Cu 31% (465g), InZn 2% (30g), totaling 1500g; wherein, in InZn, In accounts for 50% and Zn accounts for 50%.
[0062] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1350℃ and refine for 20min. When the vacuum in the furnace reaches 30Pa, turn off the vacuum pump, fill the furnace with high-purity argon, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0063] (3) Ingot casting: The furnace body is repeatedly tilted at an angle of 30 degrees for 5-7 times (mechanical stirring), and then the molten metal is poured into a water-cooled metal mold at a rate of 30g / s to produce a Φ50×76mm ingot; wherein the mold cooling water temperature is 25℃;
[0064] (4) Hot rolling: Φ50mm round billets are heated to 930℃ in a box-type resistance furnace for 30min, taken out and rapidly rolled into Φ25mm round bars in three passes;
[0065] (5) Solution treatment: Place the hot-rolled bar into a box-type heat treatment furnace, heat it to 920°C and keep it for 30 minutes, then take it out of the furnace and quickly water quench (solution treatment);
[0066] (6) Preparation of Φ21 mm rods: The solutionized Φ25 mm rods were placed in a drawing machine and cold-deformed by 30% to produce Φ21 mm round rods. The round rods were heated to 920°C in a box-type resistance furnace for 30 min and then removed from the furnace and rapidly water-quenched.
[0067] (7) Preparation of Φ16 mm rods: The Φ21 mm rods after solution treatment were placed in a drawing machine for 38% cold deformation to produce Φ16.5 mm round rods, which were then fine-drawn to the desired diameter of Φ16 mm rods;
[0068] (8) Alloy aging treatment: Place the cold-deformed round rod in a pit-type heat treatment furnace, heat it to 310°C and keep it warm for 40 minutes to obtain a rod with nanocrystals.
[0069] Example 2-1: PdAgCuMt(In+Al) alloy nanorods
[0070] The PdAgCuMt alloy bulk nanomaterial is also prepared by vacuum casting, hot and cold forging and other processes, including the following steps:
[0071] (1) Alloy ingredients: Pd 40% (600g), Ag 27% (405g), Cu 31% (465g), InAl 2% (30g), totaling 1500g; wherein, in InAl, In accounts for 50% and Al accounts for 50%.
[0072] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1350℃ and refine for 20min. When the vacuum in the furnace reaches 30Pa, turn off the vacuum pump, fill the furnace with high-purity argon, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0073] (3) Ingot casting: The furnace body is repeatedly tilted at an angle of 30 degrees for 5-7 times (mechanical stirring), and then the molten metal is poured into a water-cooled metal mold at a rate of 30g / s to produce a Φ50×76mm ingot; wherein the mold cooling water temperature is 25℃;
[0074] (4) Hot rolling: Φ50mm round billets are heated to 930℃ in a box-type resistance furnace for 30min, taken out and rapidly rolled into Φ25mm round bars in three passes;
[0075] (5) Solution treatment: Place the hot-rolled bar into a box-type heat treatment furnace, heat it to 920°C and keep it for 30 minutes, then take it out of the furnace and quickly water quench (solution treatment);
[0076] (6) Preparation of Φ21 mm rods: The solutionized Φ25 mm rods were placed in a drawing machine and cold-deformed by 30% to produce Φ21 mm round rods. The round rods were heated to 920°C in a box-type resistance furnace for 30 min and then removed from the furnace and rapidly water-quenched.
[0077] (7) Preparation of Φ16 mm rods: The Φ21 mm rods after solution treatment were placed in a drawing machine for 38% cold deformation to produce Φ16.5 mm round rods, which were then fine-drawn to the desired diameter of Φ16 mm rods;
[0078] (8) Alloy aging treatment: Place the cold-deformed round rod in a pit-type heat treatment furnace, heat it to 310°C and keep it warm for 40 minutes to obtain a rod with nanocrystals.
[0079] Example 2-2: PdAgCuMt (Zn+Al) alloy nanorods
[0080] The PdAgCuMt alloy bulk nanomaterial is also prepared by vacuum casting, hot and cold forging and other processes, including the following steps:
[0081] (1) Alloy ingredients: Pd 40% (600g), Ag 27% (405g), Cu 31% (465g), ZnAl 2% (30g), totaling 1500g; wherein, in ZnAl, Zn accounts for 50% and Al accounts for 50%.
[0082] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1350℃ and refine for 20min. When the vacuum in the furnace reaches 30Pa, turn off the vacuum pump, fill the furnace with high-purity argon, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0083] (3) Ingot casting: The furnace body is repeatedly tilted at an angle of 30 degrees for 5-7 times (mechanical stirring), and then the molten metal is poured into a water-cooled metal mold at a rate of 30g / s to produce a Φ50×76mm ingot; wherein the mold cooling water temperature is 25℃;
[0084] (4) Hot rolling: Φ50mm round billets are heated to 930℃ in a box-type resistance furnace for 30min, taken out and rapidly rolled into Φ25mm round bars in three passes;
[0085] (5) Solution treatment: Place the hot-rolled bar into a box-type heat treatment furnace, heat it to 920°C and keep it for 30 minutes, then take it out of the furnace and quickly water quench (solution treatment);
[0086] (6) Preparation of Φ21 mm rods: The solutionized Φ25 mm rods were placed in a drawing machine and cold-deformed by 30% to produce Φ21 mm round rods. The round rods were heated to 920°C in a box-type resistance furnace for 30 min and then removed from the furnace and rapidly water-quenched.
[0087] (7) Preparation of Φ16 mm rods: The Φ21 mm rods after solution treatment were placed in a drawing machine for 38% cold deformation to produce Φ16.5 mm round rods, which were then fine-drawn to the desired diameter of Φ16 mm rods;
[0088] (8) Alloy aging treatment: Place the cold-deformed round rod in a pit-type heat treatment furnace, heat it to 310°C and keep it warm for 40 minutes to obtain a rod with nanocrystals.
[0089] The composition of the PdAgCuMt alloy nanorods prepared in Example 2, Example 2-1, and Example 2-2 was tested, and the results obtained are shown in Table 3 below. The performance test results are shown in Table 4 below.
[0090] Table 3 PdAgCuMt alloy component content (wt%)
[0091]
[0092] Table 4 PdAgCuMt alloy rod properties (≮)
[0093]
[0094] Example 3: PdAgCuMt(In+Zn) alloy nanowires
[0095] This embodiment uses vacuum casting, directional solidification, drawing and other processes to prepare nanocrystalline wire, including the following steps:
[0096] (1) Alloy ingredients: Pd 41% (205g), Ag 27% (135g), Cu 30% (150g), InZn 2% (10g), totaling 500g; wherein, in InZn, Zn accounts for 50% and In accounts for 50%.
[0097] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1340℃ and refine for 20min. When the vacuum in the furnace reaches 30Pa, turn off the vacuum pump, fill the furnace with high-purity argon gas, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0098] (3) Directional solidification: The dummy rod is pushed upward from the bottom, contacted with the liquid metal, and then pulled downward. The liquid metal is crystallized and formed through a water-cooled crystallizer to produce a φ6 mm metal rod blank. The pulling speed during the downward pull is 1.4 mm / min, the cooling water temperature is 25°C, and the cooling water flow rate is 400 L / h.
[0099] (4) Solution treatment: Place the φ6 mm alloy rod blank in a box-type heat treatment furnace, heat to 920 °C and keep warm for 30 min, then take it out of the furnace and quickly water quench;
[0100] (5) Preparation of Φ5mm wire rod: The Φ6mm rod blank after solution treatment is placed in a wire drawing machine and cold-deformed by 30% to produce a Φ5mm rod blank. The rod blank is heated to 910℃ in a box-type resistance furnace and kept at this temperature for 30 minutes. It is then taken out of the furnace and rapidly water-quenched.
[0101] (6) Preparation of Φ3.9 mm wire rod: The Φ5 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 40% to produce a Φ3.9 mm rod billet. The wire billet was heated to 900°C in a box-type resistance furnace and kept at this temperature for 30 min. It was then taken out of the furnace and rapidly water quenched.
[0102] (7) Preparation of Φ3.0 mm wire rod: The Φ3.9 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 40% to produce a Φ3.0 mm rod billet. The wire billet was heated to 890°C in a box-type resistance furnace and kept at this temperature for 20 min. It was then removed from the furnace and rapidly water-quenched.
[0103] (8) Preparation of Φ2.1 mm wire rod: The Φ3.0 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 50% to produce a Φ2.1 mm rod billet. The wire billet was heated to 890°C in a box-type resistance furnace and kept at this temperature for 20 min. It was then removed from the furnace and rapidly water-quenched.
[0104] (9) Preparation of Φ1.48 mm wire rod: The Φ2.1 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 50% to produce a Φ1.48 mm wire billet. The wire billet was heated to 870-890°C in a box-type resistance furnace and kept at this temperature for 20 min. It was then taken out of the furnace and rapidly water-quenched.
[0105] (10) Preparation of wires with a size of Φ0.6 mm and below: The φ1.48 mm wire blank after solid solution is placed on a wire drawing machine for cold deformation to produce wires with a size of Φ0.6 mm and below. Subsequently, under the protection of high-purity argon, it is heated to 290-305°C and kept warm to produce fine wires with nanocrystals.
[0106] Example 3-1: PdAgCuMt (In+Al) alloy nanowires
[0107] The preparation of nanocrystalline wire by vacuum casting, directional solidification, drawing and other processes includes the following steps:
[0108] (1) Alloy ingredients: Pd 41% (205g), Ag 27% (135g), Cu 30% (150g), InAl 2% (10g), totaling 500g; wherein, in InAl, In accounts for 50% and Al accounts for 50%.
[0109] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1340℃ and refine for 20min. When the vacuum in the furnace reaches 30Pa, turn off the vacuum pump, fill the furnace with high-purity argon gas, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0110] (3) Directional solidification: The dummy rod is pushed upward from the bottom, contacted with the liquid metal, and then pulled downward. The liquid metal is crystallized and formed through a water-cooled crystallizer to produce a φ6 mm metal rod blank. The pulling speed during the downward pull is 1.4 mm / min, the cooling water temperature is 25°C, and the cooling water flow rate is 400 L / h.
[0111] (4) Solution treatment: Place the φ6 mm alloy rod blank in a box-type heat treatment furnace, heat to 920 °C and keep warm for 30 min, then take it out of the furnace and quickly water quench;
[0112] (5) Preparation of Φ5mm wire rod: The Φ6mm rod blank after solution treatment is placed in a wire drawing machine and cold-deformed by 30% to produce a Φ5mm rod blank. The rod blank is heated to 910℃ in a box-type resistance furnace and kept at this temperature for 30 minutes. It is then taken out of the furnace and rapidly water-quenched.
[0113] (6) Preparation of Φ3.9 mm wire rod: The Φ5 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 40% to produce a Φ3.9 mm rod billet. The wire billet was heated to 900°C in a box-type resistance furnace and kept at this temperature for 30 min. It was then taken out of the furnace and rapidly water quenched.
[0114] (7) Preparation of Φ3.0 mm wire rod: The Φ3.9 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 40% to produce a Φ3.0 mm rod billet. The wire billet was heated to 890°C in a box-type resistance furnace and kept at this temperature for 20 min. It was then removed from the furnace and rapidly water-quenched.
[0115] (8) Preparation of Φ2.1 mm wire rod: The Φ3.0 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 50% to produce a Φ2.1 mm rod billet. The wire billet was heated to 890°C in a box-type resistance furnace and kept at this temperature for 20 min. It was then removed from the furnace and rapidly water-quenched.
[0116] (9) Preparation of Φ1.48 mm wire rod: The Φ2.1 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 50% to produce a Φ1.48 mm wire billet. The wire billet was heated to 870-890°C in a box-type resistance furnace and kept at this temperature for 20 min. It was then taken out of the furnace and rapidly water-quenched.
[0117] (10) Preparation of wires with a size of Φ0.6 mm and below: The φ1.48 mm wire blank after solid solution is placed on a wire drawing machine for cold deformation to produce wires with a size of Φ0.6 mm and below. Subsequently, under the protection of high-purity argon, it is heated to 290-305°C and kept warm to produce fine wires with nanocrystals.
[0118] Example 3-2: PdAgCuMt (Al+Zn) alloy nanowires
[0119] The preparation of nanocrystalline wire by vacuum casting, directional solidification, drawing and other processes includes the following steps:
[0120] (1) Alloy ingredients: Pd 41% (205g), Ag 27% (135g), Cu 30% (150g), ZnAl 2% (10g), totaling 500g; wherein, in AlZn, Al accounts for 50% and Zn accounts for 50%.
[0121] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1340℃ and refine for 20min. When the vacuum in the furnace reaches 30Pa, turn off the vacuum pump, fill the furnace with high-purity argon gas, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0122] (3) Directional solidification: The dummy rod is pushed upward from the bottom, contacted with the liquid metal, and then pulled downward. The liquid metal is crystallized and formed through a water-cooled crystallizer to produce a φ6 mm metal rod blank. The pulling speed during the downward pull is 1.4 mm / min, the cooling water temperature is 25°C, and the cooling water flow rate is 400 L / h.
[0123] (4) Solution treatment: Place the φ6 mm alloy rod blank in a box-type heat treatment furnace, heat to 920 °C and keep warm for 30 min, then take it out of the furnace and quickly water quench;
[0124] (5) Preparation of Φ5mm wire rod: The Φ6mm rod blank after solution treatment is placed in a wire drawing machine and cold-deformed by 30% to produce a Φ5mm rod blank. The rod blank is heated to 910℃ in a box-type resistance furnace and kept at this temperature for 30 minutes. It is then taken out of the furnace and rapidly water-quenched.
[0125] (6) Preparation of Φ3.9 mm wire rod: The Φ5 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 40% to produce a Φ3.9 mm rod billet. The wire billet was heated to 900°C in a box-type resistance furnace and kept at this temperature for 30 min. It was then taken out of the furnace and rapidly water quenched.
[0126] (7) Preparation of Φ3.0 mm wire rod: The Φ3.9 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 40% to produce a Φ3.0 mm rod billet. The wire billet was heated to 890°C in a box-type resistance furnace and kept at this temperature for 20 min. It was then removed from the furnace and rapidly water-quenched.
[0127] (8) Preparation of Φ2.1 mm wire rod: The Φ3.0 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 50% to produce a Φ2.1 mm rod billet. The wire billet was heated to 890°C in a box-type resistance furnace and kept at this temperature for 20 min. It was then removed from the furnace and rapidly water-quenched.
[0128] (9) Preparation of Φ1.48 mm wire rod: The Φ2.1 mm wire billet after solutionization was placed in a wire drawing machine and cold-deformed by 50% to produce a Φ1.48 mm wire billet. The wire billet was heated to 870-890°C in a box-type resistance furnace and kept at this temperature for 20 min. It was then taken out of the furnace and rapidly water-quenched.
[0129] (10) Preparation of wires with a size of Φ0.6 mm and below: The φ1.48 mm wire blank after solid solution is placed on a wire drawing machine for cold deformation to produce wires with a size of Φ0.6 mm and below. Subsequently, under the protection of high-purity argon, it is heated to 290-305°C and kept warm to produce fine wires with nanocrystals.
[0130] The composition of the PdAgCuMt alloy nanowires prepared in Example 3, Example 3-1, and Example 3-2 was tested, and the results obtained are shown in Table 5 below. The performance test results are shown in Table 6 below.
[0131] Table 5 PdAgCuMt alloy component content (wt%)
[0132]
[0133] Table 6 PdAgCuMt alloy wire properties (≮)
[0134]
[0135] Example 4: PdAgCuMt(In+Zn) alloy nanoribbons
[0136] This embodiment uses vacuum casting, hot and cold rolling and other processes to prepare a nanocrystalline strip, including the following steps:
[0137] (1) Alloy ingredients: Pd 38% (190g), Ag 29% (145g), Cu 31% (155g), InZn 2% (10g), totaling 500g; wherein, in InZn, In accounts for 50% and Zn accounts for 50%.
[0138] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1320℃ and refine for 20min. When the vacuum in the furnace reaches 30Pa, turn off the vacuum pump, fill the furnace with high-purity argon gas, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0139] (3) Ingot casting: The furnace body is repeatedly tilted at an angle of 30 degrees for 5-7 times (mechanical stirring), and then the molten metal is poured into a water-cooled metal mold at a rate of 50g / s to produce a Φ30×70mm ingot; wherein the mold cooling water temperature is 25℃;
[0140] (4) Hot rolling: a Φ30×70 mm round billet is heated to 930°C in a box-type resistance furnace for 30 min, taken out and rapidly rolled into a 100×6 mm cross-section slab in three passes;
[0141] (5) Solution treatment: The rolled slab is heated to 900-930°C in a box-type resistance furnace for 30 min, then taken out of the furnace and rapidly water quenched (solution treatment);
[0142] (6) Preparation of 100 × 3.6 mm cross-section slab: The solutionized 100 × 6 mm cross-section slab was placed under a rolling mill and cold-deformed by 40% to obtain a 100 × 3.6 mm cross-section slab. The slab was heated to 930 °C in a box-type resistance furnace for 30 min and then removed from the furnace and rapidly water quenched.
[0143] (7) Preparation of 100 × 1.5 mm cross-section plates: The solutionized 100 × 3.6 mm cross-section slabs were placed in a rolling mill and cold-deformed by 60% to produce 100 × 1.5 mm plates. The plates were heated to 890 °C in a box-type resistance furnace for 20 min and then removed from the furnace and rapidly water-quenched.
[0144] (8) Preparation of strips with a thickness of 100 × 0.5 mm and below: The 100 × 1.5 mm cross-section plate after solid solution is placed under a rolling mill for cold deformation to produce strips with a thickness of 100 × 0.5 mm and below;
[0145] (9) Aging treatment: After cold deformation, the strip with a thickness of 100×0.5 mm or less is placed in a vacuum annealing furnace and heated to 300°C for 60 minutes under the protection of high-purity argon to obtain a strip with nanocrystals.
[0146] Example 4-1: PdAgCuMt(In+Al) alloy nanoribbons
[0147] This embodiment uses vacuum casting, hot and cold rolling and other processes to prepare a nanocrystalline strip, including the following steps:
[0148] (1) Alloy ingredients: Pd 38% (190 g), Ag 29% (145 g), Cu 31% (155 g), InAl 2% (10 g), totaling 500 g; wherein, in InAl, In accounts for 50% and Al accounts for 50%.
[0149] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1320℃ and refine for 20min. When the vacuum in the furnace reaches 30Pa, turn off the vacuum pump, fill the furnace with high-purity argon gas, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0150] (3) Ingot casting: The furnace body is repeatedly tilted at an angle of 30 degrees for 5-7 times (mechanical stirring), and then the molten metal is poured into a water-cooled metal mold at a rate of 50g / s to produce a Φ30×70mm ingot; wherein the mold cooling water temperature is 25℃;
[0151] (4) Hot rolling: a Φ30×70 mm round billet is heated to 930°C in a box-type resistance furnace for 30 min, taken out and rapidly rolled into a 100×6 mm cross-section slab in three passes;
[0152] (5) Solution treatment: The rolled slab is heated to 900-930°C in a box-type resistance furnace for 30 min, then taken out of the furnace and rapidly water quenched (solution treatment);
[0153] (6) Preparation of 100 × 3.6 mm cross-section slab: The solutionized 100 × 6 mm cross-section slab was placed under a rolling mill and cold-deformed by 40% to obtain a 100 × 3.6 mm cross-section slab. The slab was heated to 930 °C in a box-type resistance furnace for 30 min and then removed from the furnace and rapidly water quenched.
[0154] (7) Preparation of 100 × 1.5 mm cross-section plates: The solutionized 100 × 3.6 mm cross-section slabs were placed in a rolling mill and cold-deformed by 60% to produce 100 × 1.5 mm plates. The plates were heated to 900 °C in a box-type resistance furnace for 20 min and then removed from the furnace and rapidly water-quenched.
[0155] (8) Preparation of strips with a thickness of 100 × 0.5 mm and below: The 100 × 1.5 mm cross-section plate after solid solution is placed under a rolling mill for cold deformation to produce strips with a thickness of 100 × 0.5 mm and below;
[0156] (9) Aging treatment: After cold deformation, the strip with a thickness of 100×0.5 mm or less is placed in a vacuum annealing furnace and heated to 300°C for 60 minutes under the protection of high-purity argon to obtain a strip with nanocrystals.
[0157] Example 4-2: PdAgCuMt (Al+Zn) alloy nanoribbons
[0158] This embodiment uses vacuum casting, hot and cold rolling and other processes to prepare a nanocrystalline strip, including the following steps:
[0159] (1) Alloy ingredients: Pd 38% (190g), Ag 29% (145g), Cu 31% (155g), ZnAl 2% (10g), totaling 500g; wherein, in ZnAl, Al accounts for 50% and Zn accounts for 50%.
[0160] (2) Melting: Place the prepared PdAgCuMt alloy material in a vacuum induction melting furnace, evacuate to 2000Pa, and start heating with electricity. After the alloy is melted, keep the melting temperature at 1320℃ and refine for 20min. When the vacuum in the furnace reaches 30Pa, turn off the vacuum pump, fill the furnace with high-purity argon gas, and make the pressure of the protective atmosphere in the furnace reach 0.09-0.098MPa (slightly lower than one atmosphere);
[0161] (3) Ingot casting: The furnace body is repeatedly tilted at an angle of 30 degrees for 5-7 times (mechanical stirring), and then the molten metal is poured into a water-cooled metal mold at a rate of 50g / s to produce a Φ30×70mm ingot; wherein the mold cooling water temperature is 25℃;
[0162] (4) Hot rolling: a Φ30×70 mm round billet is heated to 930°C in a box-type resistance furnace for 30 min, taken out and rapidly rolled into a 100×6 mm cross-section slab in three passes;
[0163] (5) Solution treatment: The rolled slab is heated to 900-930°C in a box-type resistance furnace for 30 min, then taken out of the furnace and rapidly water quenched (solution treatment);
[0164] (6) Preparation of 100 × 3.6 mm cross-section slab: The solutionized 100 × 6 mm cross-section slab was placed under a rolling mill and cold-deformed by 40% to obtain a 100 × 3.6 mm cross-section slab. The slab was heated to 930 °C in a box-type resistance furnace for 30 min and then removed from the furnace and rapidly water quenched.
[0165] (7) Preparation of 100 × 1.5 mm cross-section plates: The solutionized 100 × 3.6 mm cross-section slabs were placed in a rolling mill and cold-deformed by 60% to produce 100 × 1.5 mm plates. The plates were heated to 900 °C in a box-type resistance furnace for 20 min and then removed from the furnace and rapidly water-quenched.
[0166] (8) Preparation of strips with a thickness of 100 × 0.5 mm and below: The 100 × 1.5 mm cross-section plate after solid solution is placed under a rolling mill for cold deformation to produce strips with a thickness of 100 × 0.5 mm and below;
[0167] (9) Aging treatment: After cold deformation, the strip with a thickness of 100×0.5 mm or less is placed in a vacuum annealing furnace and heated to 300°C for 60 minutes under the protection of high-purity argon to obtain a strip with nanocrystals.
[0168] The composition of the PdAgCuMt alloy nanobelts prepared in Example 4, Example 4-1, and Example 4-2 was tested, and the results obtained are shown in Table 7 below. The performance test results are shown in Table 8 below.
[0169] Table 7 PdAgCuMt alloy component content (wt%)
[0170]
[0171] Table 8 PdAgCuMt alloy strip properties (≮)
[0172]
[0173] As shown in Tables 1 to 8 above, the present invention is based on an innovative PdAgCuMt alloy (Mt is any two combinations of In, Zn, and Al, such as In+Zn or In+Al or Zn+Al). The alloy components can form an infinite solid solution structure under certain thermodynamic conditions. Therefore, the preparation of PdAgCuMt metal nanomaterials can be completed using only conventional vacuum melting furnaces, air forging hammers, two-roll mills, drawing machines, wire drawing machines, and ordinary heat treatment furnaces. The prepared PdAgCuMt metal nanomaterials have high strength, high hardness, high elasticity, high corrosion resistance, and precise resistance characteristics.
[0174] At the same time, the metal nanomaterials prepared in Example 1, Example 2, Example 3 and Example 4 were structurally characterized. Figures 1 to 4 As shown in the figure, it can be seen that a nanostructure is formed, and the grain size is between 3-10nm.
[0175] In addition to the above embodiments, it should be noted that the PdAgCuMt alloy of the present invention can be used to produce three-dimensional metal nanomaterials, and all have the high strength, high hardness, high elasticity, high corrosion resistance and precision resistance characteristics claimed above. The composition of the alloy can be Pd 38-42wt%, Ag 26-30wt%, Cu 28-32wt%, Mt 1-2wt% and inevitable impurities; wherein, the Mt is any two combinations of the three elements In, Zn, and Al, with a ratio of 1:1. Preferably, it can be Pd 38-41wt%, Ag 27-29wt%, Cu 30-31wt%, Mt 1-2wt% and inevitable impurities; wherein, the Mt is any two combinations of the three elements In, Zn, and Al. Therefore, they are not listed one by one.
Claims
1. A PdAgCuMt alloy, characterized in that: The alloy comprises the following elemental raw materials by mass fraction: Pd 38-42wt%, Ag 26-30wt%, Cu 28-32wt%, Mt 1-2wt% and inevitable impurities; wherein the Mt is a combination of any two of In, Zn and Al.
2. The PdAgCuMt alloy according to claim 1, characterized in that The alloy is prepared into a rod blank by the following steps: alloy elements are mixed in proportion and placed in a vacuum induction melting furnace, isothermally refined at 1300-1350°C for 15-20 minutes, and then directional solidification is performed to obtain the rod blank.
3. The PdAgCuMt alloy according to claim 1, characterized in that The alloy is prepared into a cylindrical billet by the following steps: alloy elements are mixed in proportion and placed in a vacuum induction melting furnace, isothermally refined at 1300-1350° C. for 15-20 minutes, and then cast into a round billet of required size.
4. A three-dimensional nanomaterial prepared based on the PdAgCuMt alloy of claim 3, characterized in that: The three-dimensional nanomaterial is a block with nanocrystals and is prepared by the following steps: hot forging, solution treatment, cold forging deformation and alloy aging treatment of a round casting to obtain a nanocrystal block; wherein the deformation amount of the cold forging deformation is 10-15%.
5. A three-dimensional nanomaterial prepared based on the PdAgCuMt alloy of claim 3, characterized in that: The three-dimensional nanomaterial is a rod with nanocrystals, which is prepared by the following steps: hot rolling, solution treatment, cold drawing deformation treatment and alloy aging treatment of round casting to obtain nanocrystal rods; wherein the deformation amount of the cold drawing deformation treatment is 20-40%.
6. A three-dimensional nanomaterial prepared based on the PdAgCuMt alloy of claim 2, characterized in that: The three-dimensional nano material is a filament alloy material with nanocrystals, and is prepared by the following steps: subjecting a rod blank to a solid solution treatment, a cold drawing deformation treatment, and an alloy aging treatment to obtain a nanocrystal rod.
7. The three-dimensional nanomaterial according to claim 8, characterized in that The temperature of the solution treatment decreases gradually from 930° C. to 870° C., and the cold drawing deformation is 30-50%.
8. A three-dimensional nanomaterial prepared based on the PdAgCuMt alloy of claim 3, characterized in that: The three-dimensional nano material is a strip material with nanocrystals, which is prepared by the following steps: subjecting a round casting blank to hot rolling, solid solution treatment, cold rolling deformation treatment and alloy aging treatment to obtain a nanocrystal rod material.
9. The three-dimensional nanomaterial according to claim 8, characterized in that The temperature of the solution treatment decreases gradually from 930° C. to 870° C., and the cold rolling deformation is 40-60%.
Citation Information
Patent Citations
Pt ALLOY FOR JEWELRY
CN107614713A
Palladium vanadium precision high-resistance alloy and preparation method thereof
CN110438364A
Palladium-based alloy ultrathin strip with high hardness and high conductivity, probe and preparation method of palladium-based alloy ultrathin strip
CN118910458A
Pd ALLOY FOR ELECTRIC-ELECTRONIC EQUIPMENT
JP2011122194A
Pivoting pin of a regulator
WO2019145434A1
Cited By
High-hardness low-resistance palladium alloy wire, manufacturing method thereof and chip testing probe
CN121737554A